Adaptasi Sistem Asuransi Kesehatan Terhadap Perubahan Pola Penyakit: Indonesia - Anis Lusiana Anggreini, Anis Lusiana Anggreini; Diva Latifah Rochmah, Diva Latifah Rochmah; Riswandy Wasir (STIKes Ibnu Sina Ajibarang, 2024)
The changing pattern of diseases poses a significant challenge to health insurance systems in Indonesia and other countries. Chronic and degenerative diseases are on the rise, placing a dual burden on healthcare systems. This study employs a literature review approach to analyze the impact of changing disease patterns on health insurance systems and adaptation strategies. Through literature method analysis, this research evaluates relevant studies pertaining to this topic. The analysis findings indicate that changing disease patterns increase healthcare service costs, influence resource allocation, and demand responsive policies. Some studies highlight the importance of enhancing affordable and effective healthcare access for chronic disease patients. From the evaluated research findings, it is concluded that recommended adaptation strategies include enhancing disease screening, collaboration between healthcare institutions and insurers, and promoting prevention programs. Best practices from advanced countries such as Singapore and Thailand underscore the importance of equity in healthcare financing and enhancing primary care services. In conclusion, changing disease patterns require swift and targeted responses from health insurance systems, focusing on prevention, accessibility, and equity in financing.